2020
DOI: 10.3390/jcm9010266
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Gonadotrophin Stimulation Induces Partial Maturation of Human Sertoli Cells in a Testicular Xenotransplantation Model for Fertility Preservation

Abstract: The future fertility of prepubertal boys with cancer may be irreversibly compromised by chemotherapy and/or radiotherapy. Successful spermatogenesis has not been achieved following the xenotransplantation of prepubertal human testis tissue, which is likely due to the failure of somatic cell maturation and function. We used a validated xenograft model to identify the factors required for Leydig and Sertoli cell development and function in immature human testis. Importantly, we compared the maturation status of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…We sought to determine the impact of gonadotrophins on AR expression in prepubertal testis grafts. Sertoli cells begin to express AR as they progress from an undifferentiated to a more differentiated status [ 32 ]. Regardless of the transplantation site and treatment received, AR expression in Sertoli cells was induced in testis tissues obtained from two donors (5 and 8 years; Figure 4 a–c,i–k), whilst its expression was maintained in transplanted testis tissues from the remaining patients across all experimental groups ( Figure 4 d–f,l–n).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We sought to determine the impact of gonadotrophins on AR expression in prepubertal testis grafts. Sertoli cells begin to express AR as they progress from an undifferentiated to a more differentiated status [ 32 ]. Regardless of the transplantation site and treatment received, AR expression in Sertoli cells was induced in testis tissues obtained from two donors (5 and 8 years; Figure 4 a–c,i–k), whilst its expression was maintained in transplanted testis tissues from the remaining patients across all experimental groups ( Figure 4 d–f,l–n).…”
Section: Resultsmentioning
confidence: 99%
“…The same authors suggested that this result could be attributed to the very few steroid-producing interstitial cells present in 12-36-month-old boys in comparison with testosterone-producing Leydig cells in the testes of young infants. Our previous study using human foetal testis xenografts supports this hypothesis; continuous gonadotrophin (hCG) stimulation for 9-12 months resulted in a significant increase in the seminal vesicle weight of host castrate mice compared with those in which hCG was withdrawn during the grafting period [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations